FORENSIC ACCOUNTING: A CASE IN POINT FOR COMBATING FINANCIAL CRIMES OF BANGLADESH - Mohobbot Ali; Sanjida Ahmed (International Journal of Accounting, Finance and Business, 2019)
Today, many countries around the world have recognized the necessity of forensic accounting and also many organizations retained forensic accountants in their organization to combat and prevent potential financial crimes. Bangladesh is not an exception to the rest of the world, where the country is losing billions of Taka in financial crimes each year. Looking into the history of fraud cases of Bangladesh, from institutional fraud like Destiney2000, Hallmark- Sonali Bank scam, Bangladesh Bank reserve heist to liquidation of People’s leasing, all these incidents raised a question in the minds of common run of people as to how the fraudsters could get away with the misappropriated money in presence of regulatory bodies? A question arises as to whether the auditors in Bangladesh are already empowered to detect such incidences ahead of time but not really motivated to do so or they are not adequately empowered to dig deeper into such occurrences due to some glass-doors. Is it right to hold auditors solely responsible for identifying the ongoing anomalies within organization? This paper scrutinizes the loopholes of existing system of Bangladesh and how forensic accounting plugs in the loopholes to combat financial crime.